Peranan Customer Satisfaction dan Customer Commitment terhadap e-WOM dalam Pengguna Aplikasi Gopay di Yogyakarta - Quelyu, Valinda Carolina De; Santoso, Singgih (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
Customer satisfaction that takes place consistently will make consumers have a commitment to a brand and can further encourage promotion through word of mouth activitie. The purpose of this study was to determine the effect of customer satisfaction on customer commitment, and the impact on consumer commitment to do e-wom activities. This research uses Gopay service as the research object and gender as the moderating variable. With the survey method on 377 respondents and the structural model testing hypotheses process, the results show that consumer satisfaction has a positive effect on consumer commitment, and consumer commitment has a positive effect on e-WOM activities; while gender is proven to moderate the relationship between these variables.